The Typology of Sasaknese Muslim Scholars’ Views in Lombok toward the Hybrid Contract as a Problem-Solving in Islamic Finance - Musawar Musawar (AL-FALAH : Journal of Islamic Economics, 2018)
This paper studies the views of Sasaknese Muslim Scholars toward the Hybrid Contract, in Lombok Island Indonesia in terms of their argumentations, typologies, and applications which becomes confusion in the society. The paper argues that problem in the transaction exists clearly. It is because of the limited meaning of Riba which is very strict that raises the society to fear to do the both in individual and group transactions since Riba have been prohibited by Al-Qur’an. While, the globalization of economic world rapidly runs which people must catch up with it. Then, related to the financial aspect of the Islamic teaching is tasted that it is running at its place. Hence, it needs to the solution. One of the solutions is applying Hybrid Contract in the view of TGH where they are very influential the life of society. Moreover, Lombok island is popularly known as thousands mosque island and soon as being seen from different references and facts. Consequently, for understanding the above phenomenon, the researcher used qualitative approach, juridical approach, and sociology by collecting data through observation, and interview to know typology Muslim scholars about hybrid contract by a hope to be the contributions for the government to take a policy. .